Availability of Prescription Opioid Disposal Bins at United States Children's Hospitals - Rabab M. Barq, MD; Laura Houshmand, MS; Olivia A. Keane, MD; Shadassa Ourshalimian, MPH; Lorraine I. Kelley-Quon, MD, MSHS (Journal of Pediatrics: Clinical Practice)
This descriptive study examined availability of prescription opioid disposal bins at US children's hospitals and assessed pharmacy-provided information on safe disposal. Only 44.2% reported a bin on site and among those without, advice varied. These findings highlight the need for improved prescription opioid disposal education and infrastructure at children's hospitals.